A novel torque teno mini virus in the blood of the patient with lymphoma. (February 2018) - Li, Wang; Yang, Shixing; Wang, Yanchun; Zhu, Wenjun; Ni, Ping; Zhu, Shuai; Xu, Juan; Lu, Renquan; Zhou, Chenglin
Aim: To characterize a novel anellovirus and analyze the relationship of the novel anellovirus with other anelloviruses.Materials & methods: Twenty-one serum samples of lymphoma patients were collected and viral metagenomics method was used to identify the novel anellovirus; CLUSTALW1.8 and MEGA6.0 was used to perform phylogenetic analysis; prevalence investigation was performed by nest PCR.Results: A novel anellovirus was discovered from two patients with lymphoma. The complete genome of torque teno mini virus (TTMV)-SHA is 2880 nt in length. Phylogenetic analysis based on ORF1 indicated that TTMV-SHA clusters with EF538882 sharing 62.5% sequence similarity, and the sequences divergence is 54%.Conclusion: TTMV (SHA) belonged to a novel anellovirus species, whether this novel anellovirus is associated with lymphoma needs further studies.